Primary breast neuroendocrine carcinoma: a case report and literature review - CHEN Jiaying; LI Yongfei; YING Yu; YAO Chang (Zhongguo linchuang yanjiu, 2024)
Objective To report a case of primary neuroendocrine breast cancer (NEBC)，and to provide clinical reference for the diagnosis and treatment of the disease. Methods The diagnosis and treatment process of a 54-year-old female patient with NEBC admitted to Jiangsu Province Hospital of Chinese Medicine on September 13, 2021 was retrospectively reported，and analyzed in combination with relevant literature. Results The patient was admitted due to unilateral painless breast mass. The patient was considered to have a non-special type of breast cancer with neuroendocrine differentiation and underwent surgery. The diagnosis of NEBC was confirmed by pathology and immunohistochemistry after operation. Further comprehensive treatment was given and no local recurrence or distant metastasis was found in the 1-year follow-up. Conclusion NEBC is a rare and special type of breast carcinoma which lacks specific clinical manifestations. Pathology and immunohistochemistry are required for diagnosis. Chromogranin A (CgA) and sunaptophysin (Syn) are generally considered to be reliable markers for the diagnosis of NEBC. The treatment plan has not yet formed a unified standard. Treatment guidelines for general type of breast cancer of the same pathological stage are mostly referred to. There is still no consensus on its prognosis.